Smoking prevention and cessation in young people. (2nd April 2021) - Croghan, Emma
Abstract : Smoking is started primarily in adolescence and is responsible for nearly 80 000 preventable deaths in England per year. Children and young people are reported to become addicted to tobacco and smoking within 4 weeks of starting the habit, In this article, Emma Croghan considers how school nurses can aid in preventing children and young people from taking up smoking, focusing on effective interventions such as mass media campaigns and school or peer-based programmes. How to help young people stop once they have developed a smoking habit is also discussed, based on the Ask, Advise, Act steps for advice sessions with young people who smoke.